Crystal structure of lacosamide form I, C13H18N2O3. Issue 3 (12th August 2015) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of lacosamide form I has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques (density functional theory). Lacosamide form I crystallizes in space group P 21 (#4) with a = 10.677 73(5), b = 4.799 68(2), c = 13.639 16(9) Å, β = 91.6331(10)̊, V = 698.719(6) Å 3, and Z = 2. Van der Waals interactions are important in the crystal structure. Two N–H···O hydrogen bonds form C1, 1(4) chains along the b -axis. Several weaker C–H···O hydrogen bonds to the ketone oxygens also contribute to the packing energy. These C–H···O extend both along the b -axis and in the ac -plane, and help link the molecules in three dimensions. The powder pattern has been submitted to International Centre for Diffraction Data for inclusion in the Powder Diffraction File™.